Electron loss in collisions of dressed projectiles with atoms and molecules. (July 2015) - Fregenal, D; Fiol, J; Bernardi, G; Monti, J M; Suárez, S G; Fainstein, P D; Rodríguez, L M; Rivarola, R D; Schuch, R
Synopsis: Energy distributions of electrons emitted with energies corresponding to the region of the electron-loss-cusp (ELP) were measured for collisions of several neutral projectiles with atoms and small molecules. Besides the well known projectile ELP cusp, a second structure is observed for Li and Na projectiles. Comparing the experimental data with four-body CTMC calculations we analise the origin of these structures in terms of nuclear-electron and electron-electron interactions.